Physiological Efficiency of Cassava as Influenced by Genotypes Over Period of Maturity in the Screening of K Use Efficient Genotypes - K. Susan John; J. Sreekumar; S.U. Shanida Beegum; Sanket J. More; M.N. Sheela; G. Suja (JOURNAL OF ROOT CROPS, 2022)
Plant nutrition of cassava is important on account of its high yield to the tune of 30-50 t ha-1. Among the major nutrients, the key nutrient, K plays a significant role in enhancing tuber yield and improving tuber quality. This relevance of K urged in undertaking research to screen K use efficient cassava genotypes with a view to reduce the external application of K. The initial evaluation of 83 elite cassava genotypes conducted at ICAR-CTCRI to exploit their physiological efficiency (PE) of K grouped the genotypes into five clusters with 9, 48, 17, 5 and 4 genotypes respectively in each cluster. The parameters contributing to PE viz., biological yield and total plant nutrient uptake were influenced by plant dry matter yield, dry matter percentage and K contents of the genotypes. This paper narrates the genetic diversity among clusters, among the intervals of maturity and their interaction as well as the significant effect of the parameters associated with PE under different clusters and stage of maturity in the identification of K efficient genotypes. The study revealed significant effect of number of storage roots and tuber length at 6 MAP under cluster 1, tuber girth at 10 MAP, leaf and stem K at 6 MAP under cluster 2, storage root dry matter percentage at 6 MAP under cluster 3, leaf and stem dry matter percentage at 8 MAP under cluster 4, storage root K at 10 MAP under cluster 5 in affecting the PE. As most of these attributes are significantly high during 6 MAP, it can be established that, screening for NUE should be done at 6 MAP. Since the tuber quality attributes being important in the selection of genotypes, the analysis indicated lowest cyanogen under cluster 2 at 10MAP and highest starch under cluster 4 at 6 MAP. Among the six genotypes identified as K efficient through preliminary evaluation, Aniyoor, 7 Sahya (2) and 7III E3-5 came under cluster 1 and W-19, CR 43-8, 6-6 under cluster 2. This information with respect to each cluster towards their contribution in influencing the inherent PE of the genotypes as well as the variability in growth stages in influencing the associated attributes can form crucial factors in selecting parent materials for breeding purpose in evolving K efficient genotypes.